In vitro and in vivo studies with tetra‐hydro‐jasmonic acid (LR2412) reveal its potential to correct signs of skin ageing. (23rd May 2013) - Tran, C.; Michelet, J.F.; Simonetti, L.; Fiat, F.; Garrigues, A.; Potter, A.; Segot, E.; Watson, R.E.B.; Griffiths, C.E.M.; de, O.
Abstract Background LR2412, a synthetic derivative of jasmonic acid, improved the reconstruction and homeostasis of our organotypic skin models. Objectives The need for efficient 'anti‐ageing' treatments, in particular for the management of photoaged skin, prompted us to investigate this new ingredient for its potential to correct signs of skin ageing in vitro and in vivo and to identify its mode of action. Results In vitro, penetration of LR2412 was evaluated using a Franz diffusion cell on excised human skin. Its exfoliating properties and interactions with the stratum corneum were studied using electron microscopy and X‐ray diffraction. Experiments were performed on a human reconstructed skin model. In vivo, the effects of LR2412 on steroid‐induced skin atrophy, a clinical skin ageing model, were assessed vs. vehicle. A patch test study evaluated its effect on deposition of fibrillin‐rich microfibrils in the papillary dermis in clinically photoaged volunteers. A clinical study on the appearance of crow's feet wrinkles was conducted over 3 months of daily application. Penetration studies revealed that LR2412 reaches viable epidermis and superficial dermis, which are skin targets of anti‐ageing actives. Within the upper layers of the stratum corneum LR2412 accelerates desquamation and improves the mechanical properties. At the dermal–epidermal junction of reconstructed skin, collagen IV, laminin‐5 and fibrillin were stimulated. In vivo, LR2412 reversed steroid‐induced atrophy. The patch test model confirms the deposition of fibrillin‐rich microfibrils, then an in use clinical study revealed that it reduced facial wrinkles. Conclusions The in vitro and in vivo data demonstrate that based on its multiple interactions within human skin, LR2412 has potential to partially correct the signs of ageing in intrinsically and photoaged skin.